2006
DOI: 10.1197/j.aem.2006.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported Pain Scores in the Emergency Department: Lack of Association with Vital Signs

Abstract: Background: Some practitioners and investigators have presumed relationships between pain scores and heart rate, blood pressure, or respiratory rate. Previous literature has not adequately addressed the association of pain and vital signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Our results are similar to those of other studies in ED, prehospital, or military settings. 25,28,36,37,39 For example, Bendall et al demonstrated, in a retrospective prehospital study, a slightly increased likelihood of severe pain if: HR is ≥100 beats/min for patients ≤ 64 years old, or if SBP was ≥140 mm Hg for patients ≥65 years old (18% and 14%, respectively). However, these authors concluded: "Simple correlation fails to show clinically important association between prehospital vital signs and pain severity."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results are similar to those of other studies in ED, prehospital, or military settings. 25,28,36,37,39 For example, Bendall et al demonstrated, in a retrospective prehospital study, a slightly increased likelihood of severe pain if: HR is ≥100 beats/min for patients ≤ 64 years old, or if SBP was ≥140 mm Hg for patients ≥65 years old (18% and 14%, respectively). However, these authors concluded: "Simple correlation fails to show clinically important association between prehospital vital signs and pain severity."…”
Section: Discussionmentioning
confidence: 99%
“…However, in the prehospital and ED literature, it is unclear how useful vital signs are for predicting pain intensity. [22][23][24][25][26][27][28][29][30] Pain intensity is subjective, and with conflicting results, researchers have tried to identify unbiased parameters (including vital signs) to validate pain intensity. HR (or HR variability), more than blood pressure, has been associated with pain intensity, [22][23][24]27,[31][32][33][34] but mostly in males.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes in physiologic measurements are not specific pain indicators and may also be associated with physical exertion, fever, and anxiety (73). Similarly, although increased changes in physiological parameters have been shown in children in pain, no correlation in children between improved pain scores and changes in respiratory rates, heart rates, or blood pressure has been demonstrated (74).…”
Section: University Of Melbourne Pain Scalementioning
confidence: 99%